Melatonin Inhibits Formation of Mitochondrial Permeability Transition Pores and Improves Oxidative Phosphorylation of Frozen-Thawed Ram Sperm - Fang, Yi; Zhao, Chengzhen; Xiang, Hai; Zhao, Xueli; Zhong, Rongzhen (Frontiers in Endocrinology, 2020)
Structural and functional damages to mitochondria of frozen-thawed sperm are a typical cryoinjury, with mitochondrial permeability transition pore (MPTP) formation being the hallmark change. Mitochondria are both a primary synthesis site and principle target for melatonin; this compound can directly inhibit MPTP formation and therefore confer protection at a mitochondrial level. The objective was to determine effects of melatonin on MPTP opening, viability, motility, and oxidative phosphorylation (OXPHOS) of frozen-thawed ram sperm. Ram semen was diluted in glucose-egg yolk buffer with 0 or 10-7 M melatonin (frozen and frozen + melatonin groups, respectively) and slow frozen, with fresh semen as Control. In frozen-thawed sperm, melatonin inhibited MPTP opening and lactate concentrations and improved sperm viability, motility, acetyl-CoA concentration and adenosine triphosphate (ATP) production. With regard to the underlying physiological mechanism, melatonin suppressed movement of citrate synthase, isocitrate dehydrogenase, oxoglutarate dehydrogenase complex and F0F1-ATP synthase permeability from mitochondrial to cytosolic fractions induced by MPTP opening; furthermore, it increased mRNA expressions of respiratory chain complex components and activities of complexes I, II, III and IV and thereby improved oxygen consumption capacity in frozen-thawed sperm. In conclusion, melatonin improved OXPHOS of frozen-thawed ram sperm, attributed to inhibition of cryopreservation-induced MPTP opening.